COVID-19 and the Nervous System - Chindo Bala Mallum; Charles Obi Achoru (Clinical Manifestations of Covid-19: A Multi-Disciplinary Approach, 2024)
The nervous system is believed to be affected at different stages of infection by the SARS-CoV2 virus which causes the corona virus infection. Various neurological manifestations of the infection have been described ranging from innocuous symptoms such as loss of smell to more severe symptoms like the development of an encephalopathy. The close relationship between COVID-19 and the nervous system is borne from the fact that the viral receptors are avidly expressed by cells in the nervous system. The risk of death from neurological complications of the virus has been described particularly for those with more severe forms of the infection. In survivors, the possibilities of long-term complications abound. This section aims to describe the effect of the SARS-CoV2 infection on both the central and peripheral nervous systems. It also tries to explain possible mechanisms of infection as well as pathogenesis.